Synthesis and Characterization of New Heterocyclic Thioxanthone Derivatives (مجلة بغداد للعلوم, 2013)
This work comprises the synthesis of new thioxanthone derivatives containing              C-substituted  thioxanthone. To obtain these derivatives, the o-mercapto benzoic acid was chosen as the starting material, o-mercapto benzoic acid with  phenoxy acetic acid / thio phenoxy acetic acid gave  2-(oxy acetic acid) thioxanthone (1) and 2-(thio acetic acid) thioxanthone (2)  respectively.  Treatment  of   (1,2)   with thionyl chloride gave      2-(oxy acetyl chloride) thioxanthone (3) and  2-(thio acetyl chloride) thioxanthone (4) respectively. Compounds (3,4) were treated with hydrazine hydrate (99%) to form the hydrazide  (5,6)  which  is  the  desired  Chiron, the hydrazide (5,6) was used   to   react    with    phenyl isothiocyanate / phenyl isocyanate    to   give  thiosemicarbazide (7,8) / semicarbazide  (9,10)  derivatives respectively, which  were  used  in  the  preparation of eight types of heterocyclic derivatives.